SHELTERS FOR INTERNALLY DISPLACED AND VULNERABLE PERSONS FROM THE ENERGY EFFICIENCY AND COMFORT POINTS OF VIEW - ДЕШКО, В. І.; ЯЦЕНКО, О. І.; ШЕВЧЕНКО, О. М.; БІЛОУС, І. Ю. (Technologies and Engineering, 2024)
Purpose. Analysis of the actual state of shelters for internally displaced and vulnerable population groups, and investigation of ways to improve the comfort and energy efficiency of shelters. Methodology. The initial survey of shelters located in different regions of Ukraine, to analyze their current state from the energy efficiency and comfort points of view, was carried out using observation and survey methods. Most shelters are part of buildings and not independent construction objects. The heat transfer resistances of enclosing structures according to DSTU 9191:2022 [1] and the energy efficiency of engineering systems according to DSTU EN 15232-1:2017 [2] were determined. Findings. Based on the survey results, proposals were made to ensure and improve comfortable and energy efficient conditions in shelters. The work also highlights aspects that require joint efforts of the authorities, public organizations and international donors to improve living conditions in shelters. Originality. Considering the lack of research on the state of shelters in Europe and actualization of these issues for Ukraine in the last two years, the analysis is both timely and relevant. It is known that the level of indoor thermal comfort has a great influence on the emotional and physical state of residents. Practical value. The issues of providing comfortable and energy efficient microclimate in shelters are equally important, especially during the heating period and massive hostile attacks on Ukraine's energy infrastructure. Therefore, the conducted research has indicated the relevance of the energy efficiency problems of shelters in Ukraine.